2014
DOI: 10.1289/ehp.1408418
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Energetics, Epigenetics, and Cellular Responses to Stress

Abstract: Background: Cells respond to environmental stressors through several key pathways, including response to reactive oxygen species (ROS), nutrient and ATP sensing, DNA damage response (DDR), and epigenetic alterations. Mitochondria play a central role in these pathways not only through energetics and ATP production but also through metabolites generated in the tricarboxylic acid cycle, as well as mitochondria–nuclear signaling related to mitochondria morphology, biogenesis, fission/fusion, mitophagy, apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
167
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(173 citation statements)
references
References 103 publications
2
167
0
4
Order By: Relevance
“…Mitochondria are multitasking organelles [28], and many environmental and stress stimuli can cause mitochondrial dysfunction [29,30], thereby affecting spermatogenesis [31][32][33][34]. The present study is a follow-up to our previous works, which showed that Sucla2 expression decreased in testes and GC1 cells with increasing apoptotic cells after exposure to endocrine disruptor BDE47 [8].…”
Section: Discussionsupporting
confidence: 73%
“…Mitochondria are multitasking organelles [28], and many environmental and stress stimuli can cause mitochondrial dysfunction [29,30], thereby affecting spermatogenesis [31][32][33][34]. The present study is a follow-up to our previous works, which showed that Sucla2 expression decreased in testes and GC1 cells with increasing apoptotic cells after exposure to endocrine disruptor BDE47 [8].…”
Section: Discussionsupporting
confidence: 73%
“…Mitochondria are dynamic organelles involved in a wide range of processes, such as ATP generation, cell death, immune signaling, chemotaxis, and calcium homeostasis (48). These organelles also play a central role in phospholipid metabolism and lipid exchange with the ER (49,50).…”
Section: Resultsmentioning
confidence: 99%
“…Considering its importance in modulating growth factor downstream pathways, we surmised that AQP8-dependent H 2 O 2 transport could be fine-tuned during stress conditions known to entail the production of ROS (51,52). Accordingly, we found that diverse cellular stresses reversibly inhibit AQP8-dependent transport, impacting cell growth and survival.…”
Section: Innovationmentioning
confidence: 96%